Evaluation of Sperm Velocity Parameters with Glutathione and Honey in Skim Milk Based Extenders by CASA on Boer Buck - Araker, Suresh; Tandle, MK; Vinay, PT; Bijurkar, RG; Suranagi, MD; Rao, Jagannath; Kulkarni , S (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The study aimed to evaluate the Boer buck sperm velocity (µm/sec) parameters (VCL: Curvilinear Velocity, VAP: Average Path Velocity and VSL: Straight line Velocity) with 5 mM Glutathione (G) and 1% or 2% Honey (H) in Skim milk (SM) based extenders preserved at refrigeration temperature for 0, 24, 48 and 72 hrs. A total of 72 ejaculates were collected equally from 6 mature bucks at the weekly interval by using Artificial Vagina (AV) as per the standard procedure. All the ejaculates were diluted using six Skim milk-based extenders, viz. SME, SMGE, SMGH(1%)E, SMGH(2%)E, SMH(1%)E and SMH(2%)E. The sperm motility was evaluated by CASA (Computer Assisted Semen Analyzer). The data obtained was statistically analyzed. The results showed that sperm velocity parameters (VCL, VAP, and VSL) differed significantly (p <0.05) from the extender to extender at 24, 48, and 72 hours of refrigeration. Supplementation of optimum concentration of glutathione (5 mM) and honey (1%) maintained better sperm velocity parameters up to 72 hours of storage compared to other extenders and was successful in the preservation of buck spermatozoa at refrigeration temperature. Hence, It was concluded that Boer buck semen could be preserved effectively with SMGH(1%)E at refrigeration temperature for sperm velocity parameters up to 72 hours of storage.